Discount Strategies and their Impact on Unplanned Purchase Behaviour of Retail Consumers - sugiat, Jajang; Islamiatiningsih, Dini (Manunggal Halim Jaya, 2023)
The increasingly fierce competition in the retail industry requires companies to develop marketing strategies that are more effective in attracting consumer attention and increasing sales. One strategy that is often applied is discounts, which are believed to influence impulse buying decisions. This study aims to analyse the effect of discounts on unplanned purchases at Alfamart Nangoh Pameungpeuk. This research uses quantitative methods with a descriptive approach. The population in this study were consumers of Alfamart Nangoh Pameungpeuk, with non-probability sampling technique using incidental sampling method. The number of samples used in this study were 68 respondents. Data collection was carried out through distributing questionnaires to respondents who met the criteria. Data analysis was carried out by testing the validity, reliability, and relationship between variables using simple correlation and regression techniques. The results showed that price discounts have a significant influence on unplanned purchases at Alfamart Nangoh Pameungpeuk. Consumers are more likely to make spontaneous purchases when they feel they benefit through discounts. This finding supports previous research which states that discount strategies can increase impulse buying behaviour. The implication of this study is that retail companies need to optimise discount strategies by considering other supporting factors, such as visual and digital promotions, in order to increase their effectiveness in attracting consumers.